Burning for biodiversity: highly resilient ant communities respond only to strongly contrasting fire regimes in Australia's seasonal tropics. Issue 5 (21st July 2014) - Andersen, Alan N.; Ribbons, Relena R.; Pettit, Magen; Parr, Catherine L.; Driscoll, Don
Summary According to the pyrodiversity paradigm, a wide range of fire regimes is required to maintain biodiversity in fire‐prone landscapes. However, the requisite level of pyrodiversity has seldom been tested and may actually be very low. Here, we examine the sensitivity of tropical savanna ants to variation in fire regimes using results from a long‐term fire experiment near Darwin, Australia. Six experimental fire regimes, with varying fire frequency and seasonality, have been applied to 18 one‐ha plots in three replicated blocks since 2004, with ants sampled prior to experimental burning and then annually after up to 2009. Our primary focus is on the extent to which different patterns of ant richness and composition are associated with each of the six treatment regimes, or whether there is such high overlap that differences only become apparent when experimental treatments are grouped to provide strongly contrasting fire regimes. When treating each of the six fire treatments separately, we were unable to detect a significant influence of fire on any ant community response variable. We were only able to detect significant ant responses when we grouped the experimental treatments into two contrasting fire frequency classes, low (burnt at most once over the 5 years) vs. high (burnt every 1 or 2 years). Even then, these responses were only evident after 3 years of fire treatment. Our findings demonstrate that ant communities have very high resilience in relation to fire, with differences evident only between strongly contrasting regimes. Such resilience appears to be characteristic of savanna ants throughout the world. Synthesis and applications. A large range of finely tuned fire regimes is unlikely to promote regional ant diversity. Rather, only very limited pyrodiversity (a combination of frequently and infrequently burnt areas) would appear to be sufficient for maintaining diversity at a landscape scale. It is important that fire management for biodiversity conservation focuses on the demonstrated requirements of target species, rather than be based on an assumption that 'pyrodiversity begets biodiversity'.